The Color Vision Disorder in Diabetic Patients - Wisam Chasib Alhamadani; Al-Ziayyir, Ali Taha Yasin; Khalid Tawfeeq Najm (Department of Opthalmology, Faculty of Medicine, Universitas Sriwijaya, 2023)
Introduction: The visible spectrum (about 400 to 700 nm) with a mosaic of three classes of photoreceptors compose the human visual system. They are sensitive to different wavelength ranges with overlapping. The receivers have high sensitivities at short wavelengths ( 440 nm), medium ( 535 nm), or longer ( 565 nm), which are S, M, and L cones, respectively. The study aimed to determine blue color vision defects in diabetes mellitus. Methods: A cross-sectional study was done at an ophthalmology clinic on 200 eyes (right and left) of patients with DM for a period of 5 one years (2021). Ishihara plates were used initially for screening. The D-15 test was performed for the evaluation of color vision. Results: The mean age of the sample was 45.66±15.65 years. The most frequent disorder visualized was tritanomaly in 63%, followed by trichromate in 27%, and the least disorder was deuteranomaly in 2%. In addition, mixed disorder is seen in 8% of cases. In relation to laterality, right eye tritanomaly was found in 34%, while the left eye was recorded in 29%. The right eye trichromate was observed in 12%, whereas the left eye was reported in 15%. The left eye deuteranomaly was reported more than the right (1.5% vs. 0.5%). Conclusion: Color vision evaluation with good screening color vision test can be detected even before clinically visible diabetic retinopathy. Early detection was helpful in the prevention of vascular changes in the retina. All diabetic patients should be given proper awareness and health education regarding color vision deficiency. Timely assessment of color vision may detect tritanomaly earlier in diabetics.